Delay-tolerant forwarding strategy for named data networking in vehicular environment. (14th May 2019) - Kuai, Meng; Hong, Xiaoyan; Yu, Qiangyuan
Named data networking (NDN) has been considered as a promising networking architecture for vehicular ad-hoc networks (VANETs). However, interest forwarding in NDN suffers severe issues in vehicular environment. Broadcast storms result in much packet loss and huge transmission overhead. Also, link disconnection caused by highly dynamic topology leads to low packet delivery ratio and extreme long delay in data retrieval. Thus, an efficient NDN forwarding strategy to retrieve data is urgently required. In this paper, we propose the density-aware delay-tolerant (DADT) interest forwarding strategy to retrieve traffic data in vehicular NDN. DADT specifically addresses data retrieval during network disruptions using delay tolerant networking (DTN). It makes retransmission decisions based on directional network density. Also, DADT mitigates broadcast storms by using a rebroadcast deferring timer. We compared DADT against other strategies through simulation and the results show that it can achieve a higher satisfaction ratio while maintaining low transmission overhead.